THE ROLE OF PRODUCTIVE ZIS, ISLAMIC WORK ETHIC, AND LENGTH OF BUSINESS ON THE WELFARE OF MSMES - Maghfiroh, Fika; Adiba, Elfira Maya (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2023)
This research aims to determine the influence of productive ZIS, Islamic work ethic and length of business on the welfare of MSMEs. This research methodology is quantitative, using multiple linear regression analysis techniques with non-probability sampling techniques with a purposive sampling approach. The sample in this study was 103 mustahik who received Productive Zakat from several zakat amil institutions in the GERBANGKERTOSUSILA area. The research results show that the calculated t value for the Productive ZIS and Length of Business variables is respectively equal to1.542 and -0.663 < t table 1.984 which means that it partially has no effect onwelfare of MSMEs, while the calculated t value for the Islamic Work Ethic variable is3.532 > t table 1.984 which means it partially has a significant effect onwelfare of MSMEs.The calculated f value (11.198) > table f value (2.70) means that the variables Productive ZIS, Islamic Work Ethic and Length of Business simultaneously influence the welfare of MSMEs. Conclusion: Simultaneously, Productive ZIS, Islamic Work Ethic, and Length of Business influence the welfare of MSMEs. Partially, the ZIS Productivity and Length of Business variables have no effect on the welfare of MSMEs. Meanwhile, the Islamic Work Ethic has a significant influence on the welfare of MSMEs.